Occurrence of concavities on the lorica of two species of Testudinella (Rotifera, Monogononta, Testudinellidae) - Coelho, Paula Nunes [UNESP]; Magalhaes Braghin, Louizi Souza; Lansac-Toha, Fabio Amodeo; Henry, Raoul [UNESP] (Revista Biota Neotropica, 2019)
Testudinella is a taxon of Rotifera broadly distributed in Brazil. In a recent collection in marginal lakes connected to the Paranapanema River (Sao Paulo, Brazil), we found specimens of Testudinella mucronata and T. patina with concavities on their lorica. The objective of this study was to describe the concavities observed in individuals of both species and discuss their possible causes. Plankton samples were collected at two sampling stations, in the pelagic (PZ) and littoral (LZ) zones of the Panema and Coqueiral lakes; both of these lakes are ultra-oligotrophic and not polluted. For T. mucronata, 4% of individuals with concavities were found in the PZ of Coqueiral lake and 50% in the LZ of Panema lake. In T. patina, the proportion of specimens with concavities corresponded to 34% in the LZ of Panema lake and 17% in PZ of Coqueiral lake. In this study, we discussed that low water temperatures, predation events and/or recent hatching are factors that may justify the concavities in the lorica of specimens of our work.
Keywords: Freshwater environments; marginal lakes; morphology; rotifers; polymorphism